EXPOSING E-PROCUREMENT FAILURES IN PREVENTING PROCUREMENT OF GOODS AND SERVICES FRAUD - Saputra, Edwin; Anis Chariri (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to reveal the failure of e-procurement in preventing fraud in the procurement of goods/ services and to explore the essence of meaning behind these fraudulent practices and behaviors. The method used is a qualitative approach using a interpretive phenomenological lens. Data collection involved in-depth interviews with a semi-structured approach to eight informants and analysis of organization documents. Data analysis using a model modified by Sanders. The findings show that the root of the problems in the procurement of goods/ services are political patronage practices and violations of procurement ethics. The procurement budget is likened to a "pizza" which has been cut into several parts and will be distributed by regional heads as patrons to supporting parties as clients. Through political patronage, the selection working group intervened to win the desired provider. These various interventions have weakened the integrity of working group which has resulted in collusion between the working group and providers who are very prone to corruption and ultimately detrimental to state or regional finances. This fraudulent behavior forms a social reality within the organization that is inconsistent with procurement ethics. This study also found that the function of prevention or early warning from the inspectorate had not gone well.